Pengaruh Suhu Tinggi Terhadap Lendutan Dan Kekakuan Balok Beton Bertulang - Edhi Wahjuni Setyowati; Wisnumurti Wisnumurti (Rekayasa Sipil, 2017)
The exposure of high temperatures which exposed reinforced concrete beams will cause damage to the cement paste as a binding component of the materials and decrease the ability of the beam. The objective of the study is to identify the high temperatures effect which exposed reinforced concrete beams (10 x 15 x 100 cm), focusing on the bending stiffness, deflection and bending capacity. The tests were conducted in some temperature variations which are 400 ˚C, 600 ˚C and 800 ˚C with the heating concept based on the slow changes of surface temperature and the convective heat transfer, the normal beam specimens (27 ˚C) were also tested as control specimens. The results show that the bending capacity decreases as the heating temperature increases, followed by the decrease of bending stiffness and also the increase of deflection before the beam reaches the first yield, then there is an increase on the bending stiffness of the beam which have been exposed by high temperature at 400 ˚C after the first yield is reached.